Sub-aortic obstruction of left ventricular outflow tract secondary to benfluorex-induced endocardial fibrosis - Catherine Szymanski; Sylvestre Maréchaux; Patrick Bruneval; Michel Andréjak; Vincent Thomas de Montpréville; Emre Belli; Christophe Tribouilloy (International Journal of Cardiology: Heart & Vasculature, 2015)
Patients exposed to benfluorex have an increased risk of restrictive organic valvular heart disease. Aortic and mitral regurgitations caused by fibrotic valve disease are the most common features observed in exposure to fenfluramine derivatives in general and benfluorex in particular. We report here, for the first time to our knowledge, a well-documented case in which obstructive sub-aortic endocardium fibrosis within the left ventricular outflow tract is related with exposure to a drug that modifies the metabolism of serotonin. It now remains to be established whether extensive fibrosis of the myocardium in addition to well-documented valvular fibrosis may develop in patients exposed to amphetamine-derived drugs affecting the serotonin system.